Dying in times of COVID-19: Experiences in different care settings – An online questionnaire study among bereaved relatives (the CO-LIVE study). (April 2022) - Yildiz, Berivan; Korfage, Ida J; Witkamp, Erica FE; Goossensen, Anne; van Lent, Liza GG; Pasman, H Roeline; Onwuteaka-Philipsen, Bregje D; Zee, Masha; van der Heide, Agnes
Background: The COVID-19 pandemic and restricting measures have affected end-of-life care across different settings. Aim: To compare experiences of bereaved relatives with end-of-life care for a family member or friend who died at home, in a hospital, nursing home or hospice during the pandemic. Design: An open observational online survey was developed and disseminated via social media and public fora (March–July 2020). Data were analyzed using descriptive statistics and logistic regression analyses. Participants: Individuals who lost a family member or friend in the Netherlands during the COVID-19 pandemic. Results: The questionnaire was filled out by 393 bereaved relatives who lost a family member or friend at home ( n  =   68), in a hospital ( n  =   114), nursing home ( n  =   176) or hospice ( n  =   35). Bereaved relatives of patients who died in a hospital most often evaluated medical care (79%) as sufficient, whereas medical care (54.5%) was least often evaluated as sufficient in nursing homes. Emotional support for relatives was most often evaluated as sufficient at home (67.7%) and least often in nursing homes (40.3%). Sufficient emotional support for relatives was associated with a higher likelihood to rate the place of death as appropriate. Bereaved relatives of patients who died at a place other than home and whose care was restricted due to COVID-19 were less likely to evaluate the place of death as appropriate. Conclusion: End-of-life care during the COVID-19 pandemic was evaluated least favourably in nursing homes. The quality of emotional support for relatives and whether care was restricted or not were important for assessing the place of death as appropriate.